Symmetric power functoriality for Hilbert modular forms - Newton, J; Thorne, JA (Princeton University, 2025)
Let F be a totally real field. We prove the existence of all symmetric power liftings of those cuspidal automorphic representations of GL2(AF) associated to Hilbert modular forms of regular weight.